MERETAS KEMBALI ISLAM BERKEADABAN DALAM BINGKAI KEMANUSIAAN ERSPEKTIFISLAM PROGRESIF - Yusdani, Yusdani (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2016)
The following article tries to discuss the formulation of a set of Islamic values ??in order to become a reference for the creation of alternative and solution regarding the equitable of society which respecting human values ??in both the global and national levels. For that reason, Moslem scholars need to formulate a set of a fresh or alternative thought and the Islamic movement to be developed in the context of human life in accordance with the global ethics such as democracy, pluralism, human rights, and true justice humanitarian. Therefore, the development of thought and the Islamic movement needs  to be integrated and transformed the values ??of Islam in the context of the values ??of equality, justice, humanity. From the work of this creative methodological expected to bring Islamic thought that is more fresh and responsive in answering the demands of the position of equality of all citizens and equitable treatment, in particular the guaranteed freedom of belief, minorities, minority both in terms of religious, economic, ethnic and so on other protected and guaranteed their rights equally and fairly.